An Epidemiological Observation of Judicious use of Antibiotics in Dhar District, M.P. (India) - Bisht, Rekha; Dabi, Arvind; Dixit, Pankaj; Mishra, Dinesh Kumar (Journal of Pharmacy Practice and Community Medicine)
Background: Antibiotic resistance is presently the gigantic challenge to the effective treatment of infections globally. It is a rapidly growing clinical problem and public health threat. Promiscuous use of antibiotics is epidemic in India and this is an affair of consequential concern. Irrational use of antibiotics can cause increase adverse drug reaction, lead to antibiotic resistance and increase the treatment cost. Antibiotic resistance unfavourably influence both clinical and financial therapeutic results, with repercussion ranging from the failure of an individual patient to respond to therapy and the need for costly and/or toxic alternative medicine to the social cost of higher morbidity and mortality rates, longer duration of hospitalization and the need for changes in empirical therapy. Analysing the antibiotics utilization pattern is significant in the context of its escalating use and its overall impact on the health care system. Materials and Methods: An observational and prospective study was conducted by interviewing (using a data collection form) the patients to evaluate the utilization of antibiotics in multispecialty hospital, Dhar district, Madhya Pradesh, India. Results: Out of 102 patients interviewed, 85 (83.33%) were prescribed antibiotics either alone or in combination with other drugs. The maximum number of patients received antibiotics belongs to the age group of 31-40 (22, 18.7%). Ciprofloxacin (25, 21.25%) was the widely prescribed antibiotics followed by metronidazole (20, 17%) penicillin (15, 12.75%), azithromycin (12, 10.2%) cephalosporin (11, 9.35%) and amoxicillin (10, 8.5%). Maximum prescriptions of antibiotics were for high grade fever (29, 24.65%) followed by gastrointestinal infection (18, 15.3%). Conclusion: Proper strategy like antibiotic policy and educational intercession are necessary to control the excessive use of antibiotics in health care settings.
Keywords: Antibiotics; Drug utilization; Antibiotic Resistance; Observational study; Prospective study.